Pengaruh Kemandirian Keuangan Daerah dan Pertumbuhan Ekonomi Terhadap Indeks Pembangunan Manusia Di Provinsi Bali - Dewi, Putu Ayu Krisna; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
RegionalKfinancial independence and economic growth to human development is one of local government target in the successful implementation of regional autonomy. By increasing Local Original Income, local governments can finance the implementation of public services to improve their welfare. In fact the original income increase is not sure can improve welfare. In addition, economic growth which is still not evenly distributed in every region causes imbalance of human development in the region with the low economic growth percentage. This happens becauseEthe government has not been able to provide public services. The purpose of this study was to determine the impact of the regional financial independence and economic growth to human development. This study used financial ratio data and multiplePlinear regression analysis. Ratio analysis.was used to determine the level of regional financiall independence at the regency / city in the province of Bali. The analysis result showed that simultaneous regional financial independence, economic growth influenced significantly on the human development index, partially regional financial independence and economic growth influenced positively on the human development index
Keywords: 9Regional Financial Independence; Economic Growth; and the Human Development Index